Pengaruh Stres Kerja Dan Konflik Kerja Terhadap Kinerja Karyawan Pada PT. Rumpun Sari Antan 2 Pati - Susanti, Diah Feri, Ahmad Mardalis, SE.,MBA (2016)
The purpose of this study was to determine the effect of work stress and conflict either partially working, and the simultaneous determination of the performance at PT. Rumpun Sari Antan 2 Pati. This research is a quantitative study with a sample size 48 and obtained using techniques rendom sample. Based on the calculation results SPSS version 21 was obtained variable job stress and work conflicts influence on employee performance partially, simultaneous, and determination R2. T test of independent variables that have the greatest significant value tehadap performance of employees is job stress. Therefore, to improve the performance of employees of PT. Rumpun Sari Antan management should provide assistance in the form of a psychiatrist, an injection of morale, and provide positive pressure to the employees.